The lying behaviors of four to six-year old children as perceived by their parents. - Pastor, Katrina R. (Animo Repository, 1999)
A study was done with fifty-four parents of four to six year old children who were currently enrolled in preschools situated in Metro Manila. The relationship between lying behavior as perceived by their parents with regards to the variables of age, gender, and socio-economic status was examined through a survey using questionnaires. The results of the study showed that there was no difference in the lying behaviors exhibited when it came to gender. The difference was seen when compared with the socio-economic status and age. The most common lying behavior in general was to deny doing something wrong. The second was to deny starting fights with siblings. The most common reason for lying in general as perceived by the parents was because of being afraid to get punished, regardless of age, gender, and socio-economic status.